Distribution of acid mucus in the bronchial mucous glands. - Kollerstrom, N (1977)
The percentage area of the bronchial glands taking up the Alcian blue (pH 2-6) stain for acid mucin was obtained from sections from the trachea and from each generation down the inferior lingular axial bronchial pathway in five non-smokers and five cigarette smokers. The mean percentage value for the smokers (59-5%) was significantly less than for the non-smokers (74-4%). The percentage increased between successive generations from the trachea by an average of 6-5. This gradient did not differ significantly between the smoking and non-smoking groups. It was not possible to attribute these differences to any specific mechanism because many interacting variables were involved which could not be measured. Nevertheless the percentage mucin retention or storage provides an introduction to consideration of these variables and their response to cigarette smoke.